1997
DOI: 10.1164/ajrccm.156.5.97-02050
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: TNF- α Release from Alveolar Macrophages and Serum Level of sIL-2R Are Prognostic Markers

Abstract: At the time of diagnosis, many sarcoidosis patients have no clinical indication for corticosteroid therapy, and prognostic parameters predicting deterioration are missing. In the present study, we investigated parameters derived from bronchoalveolar lavage (BAL) and serum in 77 patients with recently diagnosed sarcoidosis to test their predictive value. Patients were divided into a group with (Group A, n = 37) and a group without (Group B, n = 40) indications for therapy, and the course of the disease was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
2
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(165 citation statements)
references
References 30 publications
13
141
2
9
Order By: Relevance
“…However, our results suggest that additional biological signals aside from IFN contribute to disease severity and progression. Some studies have suggested higher TNF signalling predicts disease progression [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results suggest that additional biological signals aside from IFN contribute to disease severity and progression. Some studies have suggested higher TNF signalling predicts disease progression [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential pathogenic role of excess TNF-a in granulomatous disease [9,[15][16][17][18] is well documented, TNF-a does not solely account for the T-helper cell type 1 (Th-1) dominated cytokine environment in the sarcoid lung; in particular, high levels of interferon (IFN)-c have also been implicated in the pathogenesis of sarcoidosis [19]. In addition, alveolar macrophages from patients with sarcoidosis have been shown to produce interleukin (IL)-12 in addition to TNF-a, IL-1b, and IL-6 [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, several studies analysing the role of the percentage of BALF lymphocytes and the CD4/CD8 ratio have been performed with diverse results [4][5][6][7]. Since the late 1990s, however, there has been increasing evidence that neutrophilic alveolitis may play an important role in the outcome of sarcoidosis.…”
mentioning
confidence: 99%